THE GIG ECONOMY: Overview and prospects for the Philippines - Mia, Ian Benedict R. (Animo Repository, 2020)
Technology has given rise to many digital platforms that enable seamless social connections, instant transactions, and high-definition visuals and imagery, to name a few. It is amazing how far technology has brought us to where we are today. Nowadays, by using a laptop or a mobile device, we reap the benefits that come with this technological advancement. From expanding our professional networks online to learning a new recipe from an online content creator, the possibilities seem endless in a digital world. There is, however, one more aspect of our lives that is significantly impacted by this rapid change—the very nature of work. Many have encountered the term gig economy in one form or another. The term has been frequently used in mainstream media, which have highlighted its advantages and disadvantages. At its basic definition, the gig economy refers to a labor market environment wherein jobs are mostly short-term in nature, workers are predominantly independent contractors, and no traditional employer-employee relationship exists between the transacting parties (Esguerra, 2019). It is a fresh and stark contrast to traditional employment, wherein jobs involve long-term commitments and professional relationships between employers and their employees.